Analisis Risiko Usahatani Padi Organik Pada Kelompok Tani Mandiri Di Kelurahan Taratara Kecamatan Tomohon Barat Kota Tomohon - Lubis, Devi Santa Maria; Jocom, Sherly Gladys; Rengkung, Leonardus Ricky (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
This research aims to identify, assess and evaluate the main risks in organic rice farming in the Independ-ent Farmers Group in Taratara Village, West Tomohon District, Tomohon City. This research was carried out for three months from May to July 2024. The sampling method used was saturated sampling. The data used in this research is primary data by conducting a direct survey of farmer groups. Meanwhile, second-ary data was obtained from village officials. The analytical method used in this research is the Failure Mode and Effects Analysis (FMEA) method and the Pareto diagram. The research results identified three main priority risk factors for the Independent Farmer Group using the fishbone diagram, FMEA, and Pareto diagram. The first factor is the competition between organic rice products and conventional products, with an RPN (Risk Priority Number) value of 12.00 and RSV (Risk Score Value) 6.00, which is assessed based on the product price. The second factor is the organic rice marketing network with an RPN (Risk Pri-ority Number) value of 8.00 and RSV (Risk Score Value) 4.00, indicating that farmer groups have not been able to expand their marketing network. The third factor is high rainy weather, with an RPN (Risk Priority Number) value of 4.00 and RSV (Risk Score Value) 4.00, which poses a risk because it cannot be predicted or controlled by farmer groups.